Pengaruh Consumer Dissatisfaction dan Variety Seeking Terhadap Brand Switching Smartphone Merek Xiaomi ke Merek Lain Pada Mahasiswa Universitas Negeri Padang - Muhammad Apit; Rose Rahmidani (Universitas Negeri Padang, 2023)
The purpose of this study was to determine the effect of consumer dissatisfaction and variety seeking on brand switching of Xiaomi smartphones to other brands on Universitas Negeri Padang student. This type of research is causative research. The population in this study were Universitas Negeri Padang students and the determination of the number of samples in this study used the Chocran formula, namely 100 respondents from Universitas Negeri Padang students using purposive sampling technique. The type of data in this study is to uses primary data. Data was collected by distributing questionnaires to Universitas Negeri Padang students and the data analysis method using multiple regression analysis. The classical assumption test was carried out using the normality test, multicollinearity test, and heteroscedasticity test using the SPSS version 26 application. The results of this study indicate that (1) consumer dissatisfaction has a positive and significant effect on brand switching of Xiaomi smartphones to other brands, (2) variety seeking has a positive and significant effect on brand switching of Xiaomi smartphones to other brands, (3) consumer dissatisfaction and variety seeking have a positive and significant effect on brand switching of Xiaomi smartphones to other brands Universitas Negeri Padang students.